Understanding how capping protein cooperates with aPKC to maintain epithelial integrity in Drosophila imaginal disc - Mendes, Cláudia Carolina de Almeida,1986- (2010)
Tese de mestrado, Biologia (Biologia Evolutiva e do Desenvolvimento), Universidade de Lisboa, Faculdade de Ciências, 2010